Roseburia Spp.: A Marker of Health? - Tamanai-Shacoori, Zohreh; Smida, Imen; Bousarghin, Latifa; Loreal, Olivier; Meuric, Vincent; Fong, Shao Bing; Bonnaure-Mallet, Martine; Jolivet-Gougeon, Anne (Future microbiology, 2017)
The genus Roseburia consists of obligate Gram-positive anaerobic bacteria that are slightly curved, rod-shaped and motile by means of multiple subterminal flagella. It includes five species: Roseburia intestinalis, R. hominis, R. inulinivorans, R. faecis and R. cecicola. Gut Roseburia spp. metabolize dietary components that stimulate their proliferation and metabolic activities. They are part of commensal bacteria producing short-chain fatty acids, especially butyrate, affecting colonic motility, immunity maintenance and anti-inflammatory properties. Modification in Roseburia spp. representation may affect various metabolic pathways and is associated with several diseases (including irritable bowel syndrome, obesity, Type 2 diabetes, nervous system conditions and allergies). Roseburia spp. could also serve as biomarkers for symptomatic pathologies (e.g., gallstone formation) or as probiotics for restoration of beneficial flora.